Edukasi Lingkungan Fisik Sekolah Menuju Green school di SMPIT Al-Fityah Pekanbaru - Aryanti, Ervina; Septirosya, Tiara; Taslapratama, Irwan; Hera, Novita (Agrimas : Jurnal Pengabdian Masyarakat Bidang Pertanian, 2024)
Climate change and global warming, caused by increasing carbon concentrations in the air, are the most pressing environmental problems. The loss of forests causes an increase in the air's ability to absorb carbon. If this is allowed to continue, the earth's temperature will increase. On the other hand, environmental pollution continues to increase. This service program aims to provide Education about caring for the school environment. This service was carried out on September 2018. This service stage consists of 6 stages: 1. Observation. 2. Interview. 3. Counseling 4. Practical training on biopori application 5. Planting practice 6. Competition to make posters with the theme of green school activities in schools. From the results of the service it was found that the service activities carried out had provided benefits in increasing students' awareness of caring about the environment. This can be seen from the results of the pre test and post test where there is an increase in understanding of the environment by approximately 40%. From the results of the service, it is recommended to maintain the enthusiasm of students in protecting the environment, especially the school environment, under the guidance of teachers.